Pendidikan Karakter Menurut K.H. Ahmad Dahlan dan Relevansinya di Indonesia - April Dwi Wulandari (Al Hikmah, 2022)
This paper seeks to uncover the thoughts on character education of K.H. Ahmad Dahlan, which he applied, and the pattern of application in his education system. This type of research is qualitative through literature study as a technique to confirm the validity of the data. Other relevant sources can also support and enrich the required data. The findings show that the character education activities taught by K.H. Ahmad Dahlan are based on his life experience. The character exemplified by K.H. Ahmad Dahlan attitude is open-minded (not excessive or moderate), regarding the homeland, tolerant, and charitable. He studied in the environment of religious and modernistic people such as reformers in the Islamic world, including Jamaluddin Al-Afghani, Rasyid Rida, and Muhammad Abduh. However, he still adheres to the main sources of Islamic teachings, namely the Qur'an and As-Sunnah. However, in his da'wah practice, K.H. Ahmad Dahlan uses innovative methods that modern and educated people can easily accept.